Grammatical Errors of Perfekt Sentences in the Writing of 2nd Semester Students in Sprachkompetenz 2 Course - Li’munawar, Istiqlal Masfirotul; Sufriono, Mutiara Feby; Rosyidah (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
Grammatical errors often occur when learning a language. This study aims to identify the forms of errors made by students when writing essays using past tense or tempus perfekt in German. The research method used is qualitative method with content analysis data collection technique. The subjects of this study were 2nd semester students of the UM German language education study program who attended the Sprachkompetenz 2 course. Data sources were obtained from the results of essay assignments in the form of perfekt sentences about activities carried out at the end of the year. From the results of the study it can be concluded that there are 3 main forms of errors that are often made in grammatical writing errors using tempus perfekt, including: (1) position errors in the sentence, (2) inaccurate use of hilfsverb or auxiliary verb and verben or verb in the sentence, and (3) mismatch of cases used.